Integration of Literacy Programs for Children with Language Disorders - Tanjung, Tobi Bagustian; Lubis, M. Joharis; Hutagalung, Surya Masriani (International Journal of Educational Research Excellence (IJERE), 2025)
The integration of literacy programs for children with language disorders requires different actions than those for children in general. This study is qualitative research based on a narrative approach through literature studies. Literacy programs train student in reading, writing, listening, and speaking skills, as well as in using and listening to language in speaking, reading, and writing. Literacy programs for children with language disorders are different from literacy programs for normal children because children with language disorders related to speech mechanisms, such as dyslexia, alexia, or dysarthria, as well as children with psychogenic disorders, such as stuttering, spoiling, or effemination, require special care in language learning. To improve their abilities, literacy programs must begin at a habituation stage. These literacy programs include early literacy, early literacy, library literacy, media literacy, technology literacy, and visual literacy